Emanzipation der Ratio Descartes' Projekt der Naturalisierung von Wissen - Scheib, Andreas (Wissenschaftliche Buchgesellschaft (wbg), 2023)
According to the thesis of the study, Descartes' redefinition of rational discourses implies the systematically justified exclusion of theological from the field of natural rationality and its interpretation as irrational, only fideistic opinions. This also means the exclusion of transcendence from the field of possible rational discourses and has the consequence that the concept of 'God', as Descartes uses it at central points in his argumentation, can no longer be meant in the theistic-theological sense. It must therefore be stripped and purified of its theological implications and reduced to what it can still mean as mere ontological vocabulary. The study combines a historical view of the historical embedding of central Cartesian doctrines in the discussions of their time with a systematic analysis of those aspects that make meaningful talk of transcendence impossible and must therefore be understood as 'naturalistic'.